Avaliação do gerenciamento de resíduos de construção e demolição em empresas construtoras do Recife e sua conformidade com a resolução nº 307/CONAMA: estudo de caso - Pontes, Genilson Correia (2007)
To each day they increase the concerns with the preservation of the environment, and grow the challenges to establish a relation balanced with the nature to supply the necessities of the some processes of production. The industry of the civil construction cause impact to the environment in its diverse phases and mainly for the generation and the disposal of its residues. Considering the necessity of the implantation of lines of direction for effective reduction of the ambient impacts generated by the deriving residues of the civil construction the CONAMA, it established lines of direction, criteria and procedures for management of residues of the civil construction, through Resolution 307 of 05 of July of 2002. This project has as objective to evaluate the management of RC&D in the construction companies of Recife and its conformity with Resolution n º 307 of the CONAMA. In this research the inquiry method was adopted, the study of cases, and was elaborated a script to analyze the SGRC&D of the construction companies, had been elaborated Protocols of evaluation, namely: Protocol ¨A¨ that it characterizes the SGRC&D, Protocol B that was elaborated being based on the methodology Clean Workmanship, and is composed for an evaluation questionnaire and Protocol C that it was elaborated being based on Resolution n º 307 of the CONAMA and evaluates the conformity of the SGRC&D in relation to this same Resolution. Through these Protocols notes for the SGRC&D of each workmanship had been attributed, and through these notes it was gotten average generality of each SGRC&D, had been searched four companies and two workmanships for company a total of eight workmanships. Through the analysis of the Protocols it is observed that all the searched companies had tried to be fit the determination of Resolution 307 ofthe CONAMA. Through the Protocols the main characteristics of each SGRC&D of these companies had been identified, of the positive and negative factors proceeding from the implantation of the system of management RC&D. The company who got the general average greater beyond also implanting the Methodology Clean Workmanship - PE adopted one politics of not generation of residues in the workmanship seedbeds